Implementación de sistema web para mejorar la administración y calidad de servicio del albergue Entre Patas de la ciudad Chepén - Pastor Rivadeneyra, Luis Alberto (2023)
The present investigation was elaborated using ICTs, presenting a solid proposal achieving a high impact in the adoption of pets from the Entre Patas Animal Shelter in the province of Chepén. The methodology used was the Extreme Programming (XP) methodology, this methodology expedited the development of the project successfully with the expected quality, achieving a product adapted to the needs of the "Entre Patas" Animal Shelter. For the development of this project, web technologies such as NG Prime 9, Angular 9, Spring boot 2.4, Java 11, MySQL 8, AWS were used. The research design was experimental, of the pre-experimental type, with a single pretest posttest group, called pretest and posttest. The population was made up of 10 collaborators to whom a survey was applied as an instrument, validated by three experts, obtaining a value of 0.039 in the Kendall coefficient test for the agreement of judges, likewise a pilot test was carried out with 15 respondents, obtaining a Cronbach's alpha value of 0.806, demonstrating its reliability and internal validity. A chronometer was used as an instrument to measure time. For the statistical tests, the SPSS V27 software was used. In the contrasting of the research hypotheses, parametric and non-parametric tests were used after analyzing the normality of the pretest and posttest data, demonstrating that the implementation of the web system improves the administration and quality of the service of the Entre Patas de Chepén hostel. Fundamentals, techniques and good programming practices have been used, which allows system updates to be carried out more easily and to reuse sources.